E-book on light and optical instruments using PjBL and ARCS motivation for secondary school - Purwati, Umi Shalihah Putri; Widowati, Asri (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of this study is to validate the feasibility, practicality, and readability of an ARCS integrated Project Based Learning e-book on light and optical instruments for junior high school students. The research method used is Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. Data collection was carried out through observation, interviews, and questionnaires dichotomous for expert validation, and Likert scale for teacher and student assessments. The questionnaires were administered to 2 expert validators, 3 science teachers, and 15 students selected through purposive sampling. Based on the results of expert validation using a dichotomous questionnaire, all experts answered “Valid” to all items, resulting in a 100% validity score. This indicates that all aspects of the e-book meet the eligibility criteria with very high validity. The practicality test by teachers, conducted using a Likert scale questionnaire, yielded a score of 91.5%, and the readability test by students, also using a Likert scale, reached 85.06%. These results indicate that the product is very feasible and highly practical. The integration of PjBL and ARCS strategies in the e-book supports student engagement and motivation.